2022
DOI: 10.1126/sciadv.abo1272
|View full text |Cite
|
Sign up to set email alerts
|

Structural analyses of human ryanodine receptor type 2 channels reveal the mechanisms for sudden cardiac death and treatment

Abstract: Ryanodine receptor type 2 (RyR2) mutations have been linked to an inherited form of exercise-induced sudden cardiac death called catecholaminergic polymorphic ventricular tachycardia (CPVT). CPVT results from stress-induced sarcoplasmic reticular Ca 2+ leak via the mutant RyR2 channels during diastole. We present atomic models of human wild-type (WT) RyR2 and the CPVT mutant RyR2-R2474S determined by cryo–electron microscopy with overall resolutions in the range of 2.6 to 3.6 Å, and rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(72 citation statements)
references
References 82 publications
3
69
0
Order By: Relevance
“…Moreover, the RyR2 protein sequence is particularly abundant in arginine, which is a positively charged amino acid that has high aqueous pKa's (13.8 pKa) 39 indicating a strong propensity to carry charge at physiological pH affecting protein structure and function that involve electrostatic interaction and protein solvation. Therefore, the conversion of arginine to citrulline by removing the positively charged amine group (NH 2 , weak base) might have consequences on the permeation properties of the channel, facilitating Ca 2+ flux when the gate opens or affects the core and cytoplasmic shell portion of the channel, which controls the gating activity 40 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the RyR2 protein sequence is particularly abundant in arginine, which is a positively charged amino acid that has high aqueous pKa's (13.8 pKa) 39 indicating a strong propensity to carry charge at physiological pH affecting protein structure and function that involve electrostatic interaction and protein solvation. Therefore, the conversion of arginine to citrulline by removing the positively charged amine group (NH 2 , weak base) might have consequences on the permeation properties of the channel, facilitating Ca 2+ flux when the gate opens or affects the core and cytoplasmic shell portion of the channel, which controls the gating activity 40 …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the conversion of arginine to citrulline by removing the positively charged amine group (NH 2 , weak base) might have consequences on the permeation properties of the channel, facilitating Ca 2+ flux when the gate opens or affects the core and cytoplasmic shell portion of the channel, which controls the gating activity. 40 Moreover, the larger [Ca 2+ ] i transients in CIA cardiomyocytes were counteracted by the reduced myofibrillar Ca 2+ sensitivity; hence, the fractional shortening of cardiomyocytes was similar between the two groups. In our preclinical model of acute inflammatory RA, where heart remodeling might not have occurred yet, the contractility observed in vitro was not different between groups, then we did not expect to see major differences in systolic function between CIA and control in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This would place the divergent region in an exposed central position and make it easily accessible to Calpain digestion if not protected by protein interactions. Interestingly, both the joining region [25] and divergent region [26] have been reported to interact with the Ryanodine Receptor (RyR), a huge (>2.2 MDa) tetrameric SR Ca 2+ release channel in JMCs [27][28][29]. These JP2-RyR interactions may protect JP2 against Calpain cleavage by covering the Calpain cleavage sites (Figure 1).…”
Section: Calpain-specific Cleavage Sites Of Jp2 and Its Structural En...mentioning
confidence: 99%
“…Heterozygous CPVT mutant RyR2-R2474S mice exhibit exercise-induced ventricular arrhythmias, and sudden cardiac death, which can be prevented by treatment of the mice with Rycals (3,11,16,18). We recently solved the structure of RyR2-R2474S and showed that it is in a primed state (Figure 2) that renders it more easily activated, accounting for the diastolic SR Ca 2+ leak that triggers the fatal arrhythmias (19).…”
Section: Introductionmentioning
confidence: 99%